Kyasanur Forest disease virus infection activates human vascular endothelial cells and monocyte-derived dendritic cells - Sirmarova, Jana; Salat, Jiri; Palus, Martin; Hönig, Vaclav; Langhansova, Helena; Holbrook, Michael R; Ruzek, Daniel (Emerging microbes & infections, 2018)
Kyasanur Forest disease virus (KFDV) is a highly pathogenic tick-borne flavivirus enzootic to India. In humans, KFDV causes a severe febrile disease. In some infected individuals, hemorrhagic manifestations, such as bleeding from the nose and gums and gastrointestinal bleeding with hematemesis and/or blood in the stool, have been reported. However, the mechanisms underlying these hemorrhagic complications remain unknown, and there is no information about the specific target cells for KFDV. We investigated the interaction of KFDV with vascular endothelial cells (ECs) and monocyte-derived dendritic cells (moDCs), which are key targets for several other hemorrhagic viruses. Here, we report that ECs are permissive to KFDV infection, which leads to their activation, as demonstrated by the upregulation of E-selectin, intercellular adhesion molecule 1, and vascular cell adhesion molecule 1 at the mRNA and protein levels. Increased expression of these adhesive molecules correlated with increased leukocyte adhesion. Infected ECs upregulated the expression of interleukin (IL)-6 but not IL-8. Additionally, moDCs were permissive to KFDV infection, leading to increased release of IL-6 and tumor necrosis factor-α. Supernatants from KFDV-infected moDCs caused EC activation, as measured by leukocyte adhesion. The results indicate that ECs and moDCs can be targets for KFDV and that both direct and indirect mechanisms can contribute to EC activation.
Keywords: RNA, Messenger; Endothelial Cells; endoteliální buňky; Tumor Necrosis Factor-alpha; Interleukin-8; Cadherins; Antigens, CD; CD antigeny; Interleukin-6; Encephalitis Viruses, Tick-Borne; mezibuněčná adhezivní molekula-1; dendritické buňky; Intercellular Adhesion Molecule-1; kultivované buňky; Kyasanur Forest Disease; lidé; interleukin-6; Humans; cévní buněčněadhezivní molekula-1; kadheriny; interleukin-8; TNF-alfa; Cells, Cultured; viry klíšťové encefalitidy; Dendritic Cells; messenger RNA; Vascular Cell Adhesion Molecule-1; nemoc kyasanurského lesa